Identification and characterization of an ABA‐activated MAP kinase cascade in Arabidopsis thaliana. (April 2015) - Danquah, Agyemang; de Zélicourt, Axel; Boudsocq, Marie; Neubauer, Jorinde; Frei dit Frey, Nicolas; Leonhardt, Nathalie; Pateyron, Stephanie; Gwinner, Frederik; Tamby, Jean‐Philippe; Ortiz‐Masia, Dolores; Marcote, Maria J.; Hirt, Heribert; et al.
Summary Abscisic acid (ABA) is a major phytohormone involved in important stress‐related and developmental plant processes. Recent phosphoproteomic analyses revealed a large set of ABA‐triggered phosphoproteins as putative mitogen‐activated protein kinase (MAPK) targets, although the evidence for MAPKs involved in ABA signalling is still scarce. Here, we identified and reconstituted in vivo a complete ABA‐activated MAPK cascade, composed of the MAP3Ks MAP3K17/18, the MAP2K MKK3 and the four C group MAPKs MPK1/2/7/14. In planta, we show that ABA activation of MPK7 is blocked in mkk3‐1 and map3k17mapk3k18 plants. Coherently, both mutants exhibit hypersensitivity to ABA and altered expression of a set of ABA‐dependent genes. A genetic analysis further reveals that this MAPK cascade is activated by the PYR/PYL/RCAR‐SnRK2‐PP2C ABA core signalling module through protein synthesis of the MAP3Ks, unveiling an atypical mechanism for MAPK activation in eukaryotes. Our work provides evidence for a role of an ABA‐induced MAPK pathway in plant stress signalling.